Zakaj (in kako) ukiniti sistem doplačil in dopolnilno zdravstveno zavarovanje? - Mišič, Luka (Delavci in delodajalci, 2020)
On Wednesday, January 29th 2020, the Slovenian Parliament declined, with 32 votes in favour and 51 votes against, the proposed amendment of the Healthcare and Health Insurance Act (ZZVZZ). The Act amending the Healthcare and Health Insurance Act (ZZVZZ-O), stipulated the abolition of co-payments and supplementary (also referred to as "complementary" when "supplementary" coincides with the term "additional") health insurance, which offers insurance against out-of-pocket- -payments covering the difference to the full value of health services provided only in part on behalf of the mandatory health insurance. The failed proposal mirrored a recent several month long debate on the abolition of co-payments and voluntary insurance for co-payments, introduced more or less in its current form by ZZVZZ-C back in 1998 when a specialized insurance company was established on its grounds. It seems as if time has come, due to the recent rejection of a new proposal, for a renewed debate not only about the legality and sensibleness but also about social justice or fairness concerning the abolition of the system of co-payments and supplementary health insurance.
Keywords: dopolnilno zdravstveno zavarovanje; obvezno zdravstveno zavarovanje; socialna varnost; socialno pravo; zdravstveno varstvo; zdravstveno zavarovanje